2020
DOI: 10.1016/j.ijpharm.2020.119166
|View full text |Cite
|
Sign up to set email alerts
|

Nasal delivery of nanosuspension-based mucoadhesive formulation with improved bioavailability of loratadine: Preparation, characterization, and in vivo evaluation

Abstract: The unique requirements of poorly water-soluble drug delivery have driven a great deal of research into new formulations and routes of administration. This study investigates the use of nanosuspensions for solubility enhancement and drug delivery. Simple methods were used to prepare nasal formulations of loratadine based on nanosuspension pre-dispersion with sodium hyaluronate as a mucoadhesive agent. The nanosuspension was prepared by antisolvent precipitation method followed by ultrasonication and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The intranasal delivery system has been evaluated for vaccination against respiratory viruses such as influenza and CoVs [ 176 , 177 ]. Nanoparticle-Mediated delivery systems have the following benefits—free from enzyme degradation; long-term existence, release and retention within the system; amicable co-delivery with adjuvants; specific targeting of cells through receptor-ligand interactions; and potentiation of the immune system [ 178 , 179 ].…”
Section: Effects Of Nanoparticles On Coronavirusesmentioning
confidence: 99%
“…The intranasal delivery system has been evaluated for vaccination against respiratory viruses such as influenza and CoVs [ 176 , 177 ]. Nanoparticle-Mediated delivery systems have the following benefits—free from enzyme degradation; long-term existence, release and retention within the system; amicable co-delivery with adjuvants; specific targeting of cells through receptor-ligand interactions; and potentiation of the immune system [ 178 , 179 ].…”
Section: Effects Of Nanoparticles On Coronavirusesmentioning
confidence: 99%
“…Mucoadhesive polymers such as hydroxypropyl methylcellulose 15,000 (HPMC K15M), carbopol 974P and sodium alginate were used in a mixture to increase the residence time of formulation at site of action. 12,13 In this study, COVID-19 patients treated with an ivermectin mucoadhesive nanosuspension nasal spray showed shorter duration of fever, dyspnea, cough, and anosmia but not GIT symptoms duration. Additionally, the findings of the current study revealed that patients with COVID-19 treated with ivermectin showed more significant reduction in measured hematological and biochemical parameters towards normal values with rapid viral clearance as evidenced by conversion of nasopharyngeal swab to negative.…”
mentioning
confidence: 57%
“…Saindane et al incorporated a carvedilol-containing nanosuspension into in situ gel, 40 and Alshweiat et al prepared a loratadine-based nasal nanosuspension to improve bioavailability. 12 SARS-CoV-2 invades the oropharynx and nasopharynx, from which it transmits even before any signs appear. The first symptoms (odynophagia, anosmia, dry cough, fever) and lung parenchyma colonization occur when the virus replicates in this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations